Pengaruh Penerapan Model Contextual Teaching Learning (CTL) Berbantuan Media Diorama Terhadap Kemampuan Berpikir Kritis Siswa Kelas V pada Pembelajaran IPA - Lofera Firiani; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
One of the skills that must be possessed in the development of the 21st century is critical thinking skills. To improve critical thinking skills, an appropriate learning model is needed. . The purpose of this study are determine the influence of the diorama media-assisted Contextual Teaching and Learning learning model on critical thinking skills in elementary science learning. The method used in this study was an experimental method while the research design of this study uses Quasi-Experiment. The data for this study were obtained from collected with an instrument in the form of a test consisting of ten multiple-choice questions and five validated description questions. The data obtained were analyzed using normality and homogeneity tests. Test Pair Sample T-Test and Independent Sample Test T-Test for dimensions of critical thinking ability to identify problems, collect relevant information, make problem solving and make conclusions obtained Sig. (2-tailed) 0.000 < 0.05. Meanwhile, for the N-Gain test, the ability dimension to identify problems by 49% in the medium category, the ability dimension to collect various relevant information by 44% in the medium category, the ability to make problem solving dimension by 39% in the medium category, and the ability to make conclusions dimension by 41% in the medium category. The results of this study suggest that by using the diorama assisted Contextual Teaching and Learning (CTL) model can improve students' critical thinking skills in Class V science learning.